2017
DOI: 10.3892/ol.2017.7342
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lapatinib on cell proliferation and apoptosis in NB4 cells

Abstract: Acute promyelocytic leukemia (APL), characterized by the presence of the promyelocytic leukemia (PML)-retinoic acid α receptor (RARα) fusion protein, responds to treatment with all-trans retinoic acid (ATRA) and arsenic trioxide (ATO). However, drug resistance and side effects restrict the application of these reagents. Hence, the development of novel therapeutic drugs for APL treatment is critical. Lapatinib, a small-molecule tyrosine kinase inhibitor, has been used in the treatment of different tumors. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…In line with our findings, several studies have demonstrated the apoptotic behavior of quinazoline derivatives through upregulating the proapoptotic genes and downregulating the antiapoptotic genes [33][34][35]. In particular, quinazoline-based anticancer drugs such as lapatinib and gefitinib were found to inhibit cancer cells growth through increasing the Bax and caspases gene levels and downregulating Bcl-2 levels, which is consistent with our finding in this study [36,37]. RT-PCR analysis of apoptotic related genes.…”
Section: Effect Of Compounds 4d and 4f On Apoptosis Regulatory Markerssupporting
confidence: 92%
“…In line with our findings, several studies have demonstrated the apoptotic behavior of quinazoline derivatives through upregulating the proapoptotic genes and downregulating the antiapoptotic genes [33][34][35]. In particular, quinazoline-based anticancer drugs such as lapatinib and gefitinib were found to inhibit cancer cells growth through increasing the Bax and caspases gene levels and downregulating Bcl-2 levels, which is consistent with our finding in this study [36,37]. RT-PCR analysis of apoptotic related genes.…”
Section: Effect Of Compounds 4d and 4f On Apoptosis Regulatory Markerssupporting
confidence: 92%
“…The former is approved for 2-year-old children and older in relapsed APL expressing CD33, whereas tamibarotene is still under investigation. Small molecule inhibitors with targets such as tyrosine kinases, telomerase, and c-myc have demonstrated some efficacy in preclinical studies using APL cell lines but have not yet advanced to clinical trials [70][71][72][73].…”
Section: Treatment Advancesmentioning
confidence: 99%
“…Consistent with other reports [52,53], we observed that Tz, T-DM1, and Lp decreased cell viability in both cell lines. It has been evidenced that the mechanism of cell viability inhibition by anti-HER2 drugs results from cell cycle arrest and increased apoptosis [54][55][56]. We noted that Tz and T-DM1, administered as a single agent, produced minimal inhibition, but their combination with Lp resulted in a potentiated effect.…”
Section: Discussionmentioning
confidence: 73%